Pengembangan LKPD Berbasis Scientific Approach pada Materi Bakteri untuk Meningkatkan Penalaran Ilmiah Peserta Didik Kelas X SMA Negeri 4 Maluku Tengah: (Development of Student Worksheets Based on Scientific Approach on Bacteria Concept for to Improving the Scientific Reasoning of Students Class X SMA Negeri 4 Central Molucas) - Masihu, Junardin Muhamad; Soisa, Yessi; M. Mesasail, Karel; Rumengan, Yuliana (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
Biology education plays a crucial role in improving scientific reasoning, yet the 2022 PISA results show that Indonesian students' scientific reasoning abilities remain low (ranked 60 out of 65). Similar issues were found at State Senior High School 4 of Central Maluku, where indicators such as fact evaluation (30%) and variable control (26%) were suboptimal due to limited teaching materials. This study aims to develop and test the effectiveness of a Scientific Approach-based Student Worksheet (LKPD) on the concept of bacteria to improve these abilities. Using the Plomp and Nieveen development model (five phases: initial investigation to implementation), this study involved subject matter experts, media experts, language experts, practitioners, and 20 10th-grade students as subjects. The instruments used included validation sheets, response questionnaires, and limited trials. The results showed that the developed LKPD was of high quality, with validity levels from subject matter experts (100%), media experts (97%), and language experts (91%) categorized as Very Valid. The practicality test by teachers reached 88% (Very Practical), and student responses were 98% (Very Feasible). Based on effectiveness testing, the use of Scientific Approach-based worksheets (LKPD) proved significant, improving students' scientific reasoning by 73.06%. These worksheets were declared valid, practical, and effective as alternative biology teaching materials. Abstrak. Pendidikan biologi berperan penting dalam meningkatkan penalaran ilmiah, namun hasil PISA 2022 menunjukkan kemampuan penalaran ilmiah siswa Indonesia masih rendah (peringkat 60 dari 65). Masalah serupa ditemukan di SMA Negeri 4 Maluku Tengah, di mana indikator seperti evaluasi fakta (30%) dan kontrol variabel (26%) belum optimal akibat keterbatasan bahan ajar. Penelitian ini bertujuan mengembangkan dan menguji efektivitas LKPD berbasis Scientific Approach pada konsep bakteri untuk meningkatkan kemampuan tersebut. Menggunakan model pengembangan Plomp dan Nieveen (lima fase: investigasi awal hingga implementasi), penelitian ini melibatkan ahli materi, media, bahasa, praktisi, serta 20 siswa kelas X sebagai subjek. Instrumen yang digunakan meliputi lembar validasi, angket respon, dan uji coba terbatas.Hasil penelitian menunjukkan bahwa LKPD yang dikembangkan sangat berkualitas dengan tingkat validitas dari ahli materi (100%), media (97%), dan bahasa (91%) berkategori Sangat Valid. Uji kepraktisan oleh guru mencapai 88% (Sangat Praktis), dan respon peserta didik sebesar 98% (Sangat Layak). Berdasarkan uji efektivitas, penggunaan LKPD berbasis Scientific Approach terbukti signifikan karena mampu meningkatkan penalaran ilmiah peserta didik sebesar 73,06%. LKPD ini dinyatakan valid, praktis, dan efektif sebagai alternatif bahan ajar biologi.